Development of Guided Inquiry-Based Chemistry Instructional Materials to Train Science Process Skills - Nurtikasari, Ayu Wika; Cahyaningrum, Sari Edi; Ibrahim, Muslimin (Studies in Philosophy of Science and Education, 2023)
The purpose of this research is to produce guided inquiry learning tools that are feasible in terms of validity, practicality, and effectiveness in training students' science process skills in acid-base material. This study refers to the Research and Development (R&D) research design. The device was implemented in class XI MIA I and XI MIA II Bani Ali Mursyad PSM Banaran with a total of 58 students. The results of this study indicate: (1) The validity of the device is in the very good category: the learning implementation plan (RPP) is in the very good category, the student worksheets (LKPD) are in the very good category, the syllabus is very good, the assessment sheets are in the very good category. (2) The practicality of learning devices is in the very practical category based on the results of the implementation of the lesson plans. (3) The effectiveness of learning devices is categorized as effective based on the N-gain test of student learning outcomes. (4) Achievement of process skills based on the results of LKPD and observation sheets categorized as skilled. Based on the results of the research, it shows that the learning tools are in the very good category, very practical, effective and skilled so that the learning tools are feasible to use.